Use of digital tools in sustainable rice production in the Mekong Delta, Vietnam - Barnard, Jennifer; Cuong, Ong Quoc; Vu, Trang; Nelson, Katherine (International Rice Research Institute, 2023)
This report summarizes findings from a study on digital tool use among rice farmers in Vietnam for the Inclusive Digital Tools Project (ATDT) of the Agroecological Transitions for Building Resilient and Inclusive Agricultural and Food Systems (TRANSITIONS) program. Results show that few digital tools focused on rice production in Vietnam provide technical advice and performance assistance. Few of the surveyed farmers use agriculture-specific digital apps for rice farming but a majority are interested in using mobile apps for farming needs, indicating that (i) farmers have limited access to rice apps, (ii) there is a gap between farmers’ needs and what the tools are offering, or (iii) the existing apps are not in the form that farmers are comfortable using. Face-to-face interactions with field agents are the most common and trusted methods for technical advice and performance assessment for farmers, indicating digital tools should support and not replace face-to-face exchanges. The majority of farmers with access to agricultural applications are male (over 90%) because men are typically the ones who directly engage in rice farming in the Mekong provinces. This suggests that an analysis of gender roles in agriculture production may be necessary to identify the areas where women are more involved and advise the development of gender-inclusive digital tools. These findings provide insights for developing inclusive digital tools for rice production that meet farmers’ needs and supplement existing methods of technical advice and performance assistance. Keywords: rice production, agroecology, inclusive digital tools, climate change, digital extension tools, social inclusion